Biomatrix from goat-waste in sponge/gel/powder form for tissue engineering and synergistic effect of nanoceria. (17th February 2021) - Singh, Hemant; Purohit, Shiv Dutt; Bhaskar, Rakesh; Yadav, Indu; Bhushan, Sakchi; Gupta, Mukesh Kumar; Gautam, Sneh; Showkeen, Muzamil; Mishra, Narayan Chandra
Abstract: For tissue engineering (TE), decellularized matrices gained huge potential as they consist of natural biomolecules which help in cell attachment and proliferation. Among various animal tissues, goat tissue has gained least attention in spite of the fact that goat tissue is less susceptible to disease transmission as compared to cadaveric porcine and bovine tissue. In this study, goat small intestine submucosa (G-SIS) was isolated from goat small intestine (G-SI), a waste from goat-slaughterhouse, and decellularized to obtain decellularized G-SIS (DG-SIS) biomatrix in the form of powder, gel and sponge form, so that it can be used for healing various types of wounds. Further, nanoceria (NC), owing to its free radical scavenging, anti-inflammatory, antibacterial and angiogenic properties, was incorporated in the DG-SIS in to fabricate DG-SIS/NC nanobiocomposite scaffold, which may exhibit synergistic effects to accelerate tissue regeneration. The scaffolds were found to be hydrophilic, biodegradable, haemocompatible, biocompatible, antibacterial and showed free radical scavenging capability. The scaffold containing NC concentration (500 µg ml −1 ) depicted highest cell (fibroblast cells) adhesion, MTT activity and free radical scavenging as compared to the DG-SIS and other nanobiocomposite scaffolds. Thus, DG-SIS/NC3 (NC with concentration 500 µg ml −1 ) scaffold could be a potential scaffold biomaterial for skin TE application.